Influences of presowing treatments on the germination and emergence of fig seeds (Ficus carica L.) - doi: 10.4025/actasciagron.v34i3.13392 - Oguzhan Çalişkan; Kazim Mavi; Aytekin Polat (Acta Scientiarum. Agronomy, 2011)
Seed germination of fig seeds is important for obtain seedlings with high variability in breeding studies, and for producing mosaic virus-free seedlings. This experiment was carried out to evaluated the effects of several treatments (priming with water for 24h, GA3 at 500 and 1000 ppm for 24h, 3% KNO3 for 24h, and stratification at 4°C for 7, 14 and 21 days) on seed germination and emergence of ‘Bursa Siyahı’ and ‘Sarılop’ fig cultivars. The application of GA3 increased the germination and emergence of these fig seeds. The highest percentages of germination and emergence were obtained with GA3 at 500 or 1000 ppm for both cultivars. The seed germination and emergence of the cultivar ‘Bursa Siyahı’ were higher than observed with the ‘Sarılop’. The application of GA3 at 500 ppm or 1000 ppm reduced the time to germination and emergence from the seeds of both cultivars. In summary, the GA3 treatments showed efficacy to overcome the dormancy of these fig seeds.